Translingualism and intercultural narratives in Kiana Davenport’s “House of Many Gods” - Semyon Sergeevich Galaktionov; Zoya Grigor'evna Proshina (Russian Journal of Linguistics, 2023)
Language and culture contacts resulting from the migration of population, as well as current geopolitical and technological processes, enhance the increase of translingual works that reveal symbiotic phenomena of languages and cultures in contact. However, there are still many unsolved problems in defining the translingual discourse and linguistic devices for creating it. The article discusses intercultural narratives in a novel by Kiana Davenport, an American author of Hawaiian descent, whose literary creative translingual work is enhanced by intercultural phenomena related to the contacts of American English, Hawaiian, and Russian languages. The article aims to describe linguistic devices for creating translingualism and to characterize the processes that take place in assimilation and language alteration in contact situations. The research has revealed that translinguality characterizes not only texts that are written in a second language, as is a traditional point of view, but also writings of a bilingual with two native languages enhanced by a third one. Translinguality can be reached by various linguistic tools comprising lexical borrowings, including endonymic toponyms and culture-specific concepts, loan translations, allusions, as well as pidginization of speech and some others. The findings showed that pidginization of speech of different characters results in stylized dialogues with deviated articulation of English words, intentional grammatical deviations, set expressions from Hawaiian Pidgin and wordplay. The results of the paper expand the idea of translingualism and intercultural communication and can be used for further research into linguistic and cultural contacts.